Advanced Asymptomatic Carotid Disease and Cognitive Impairment: An Understated Link? - Irena Martinić-Popović; Arijana Lovrenčić-Huzjan; Vida Demarin (Stroke Research and Treatment)
Advanced carotid disease is known to be associated with symptomatic cerebrovascular diseases, such as stroke or transient ischemic attack (TIA), as well as with poststroke cognitive impairment. However, cognitive decline often occurs in patients with advanced carotid stenosis without clinically evident stroke or TIA, so it is also suspected to be an independent risk factor for dementia. Neurosonological methods enable simple and noninvasive assessment of carotid stenosis in patients at risk of advanced atherosclerosis. Cognitive status in patients diagnosed with advanced carotid stenosis is routinely not taken into consideration, although if cognitive impairment is present, such patients should probably be called symptomatic. In this paper, we discuss results of some most important studies that investigated cognitive status of patients with asymptomatic advanced carotid disease and possible mechanisms involved in the causal relationship between asymptomatic advanced carotid disease and cognitive decline.